Integrated Photonic-Assisted Signal Processing and Thermal Crosstalk - De, Souvaraj; Mandalawi, Younus; Das, Ranjan; Weizel, Maxim (Metrology for THz Communications)
Integrated photonic-assisted signal processing has multiple applications such as signal amplification, multiplexing, and high-Q filtering in optical communication systems, optical sensing systems, and also microwave photonics. We will review recent works on integrated photonic-assisted signal processing for sinc-shaped Nyquist pulse generation, high-bandwidth Nyquist signal detection with low bandwidth devices, arbitrary waveform generation and measurement, and on-chip photonic frequency decoding. However, in such photonic integrated circuits (PICs), the photonic components are placed very close to each other on the chip, resulting in thermal crosstalk which degrades the system performance. Air-filled oxide and deep trench designs have proven to be very effective in mitigating the thermal crosstalk for various frequently deployed photonic devices like Mach-Zehnder modulators (MZMs), ring resonators, optical switches, and photodetectors designed on a standard silicon-on-insulator (SOI) platform. In this chapter, we will additionally review the basics of optical signal processing and some results for such trench-enhanced thermal crosstalk resilient circuits.

Integrated Photonically Assisted Samplers - Weizel, Maxim; Bahmanian, Meysam; Scheytt, J. Christoph (Metrology for THz Communications)
High-speed ADCs operating in the tens of gigahertz up to potentially terahertz range are largely constrained by the jitter in their clock sources. By incorporating photonically assisted samplers that exploit the ultralow jitter of specific mode-locked lasers (MLLs) as analogue ADC frontends, the performance limits of data converters can be pushed to achieve unprecedented levels of accuracy. Continuous advancements in electronic-photonic integration (silicon photonics) are clearing the path for integrating these systems on a chip scale, thereby leading to increased scalability, as well as reduced cost and power consumption.

Simulation and Modelling of Electronic and Photonic Components - Wrana, Dominik; Weizel, Maxim; Haussmann, Simon; Bahmanian, Meysam; Kallfass, Ingmar; Scheytt, J. Christoph (Metrology for THz Communications)
This chapter explores the crucial role of simulation and modelling of electronic and photonic components for terahertz (THz) systems. THz-related challenges already begin with setting up the signal generation and sampling parameters and continue with the realistic modelling of the electronic and photonic building blocks. Hereby, photonic components require not only the modelling of the optical signal propagation but also the modelling of the electronic interface in the THz regime. Furthermore, when advancing to the simulation of systems like fully integrated electronic transmit and receive frontends or photonically assisted analogue-to-digital converters (ADCs), it is up to the designer to find a suitable level of abstraction. Size, complexity, and available computational power versus accuracy must be taken into consideration and prioritized against each other.

A 128 GS/s 2x Time-Interleaved Track and Hold Amplifier in 130nm SiGe BiCMOS - Weizel, Maxim; Malavalli Nagaraju, Harshan Gowda; Scheytt, J. Christoph (2025 IEEE BiCMOS and Compound Semiconductor Integrated Circuits and Technology Symposium (BCICTS))

High Voltage (5Vpp) Driver Monolithically Integrated with Thermally Tunable Optical Ring Resonators in a Silicon Photonics Technology - Weizel, Maxim; Gudyriev, Sergiy; Zazzi, Andrea; Müller, Juliana; Schwabe, Tobias; Witzens, Jeremy; Scheytt, J. Christoph (2025 32nd IEEE International Conference on Electronics, Circuits and Systems (ICECS))

Photonically Assisted Sampling Circuits - Weizel, Maxim; Scheytt, J. Christoph

Optically clocked switched-emitter-follower THA in a photonic SiGe BiCMOS technology - Weizel, Maxim; Scheytt, J. Christoph; Kärtner, Franz X.; Witzens, Jeremy (Optics Express)